Liminal urbanisation: Undoing interior settler colonialism through the disruption of urban homogeneity - Goran Ivo Marinovic (Research in Globalization)
In Mediterranean cities, settler colonial urbanisation operates through spatial homogenisation that transforms difference into otherness. Since 1979, in Budva, Montenegro, low-income working-class and forced migrants have confronted settler colonial urban practices—a system wherein established residents leverage local identity and political power to exclude newcomers. Interior settler colonialism constitutes a mode of domination characterised by the aspiration of an established collective to expel immigrants from the city. Rather than merely enduring displacement, these communities transform their marginalisation into resistance through what I term “liminal urbanisation.” Through inhabiting interstitial spaces, physically marginal neighbourhoods challenge the Manichean divisions between “legitimate” residents and “others.” These traced spatial, cultural, and social heterogeneities transcend the dualistic worldview of Manichean urbanisation—a political construct wherein privileged citizens, defined by local identity, economic stability, and political empowerment, assert their authority to govern urban territories at the expense of marginalised groups. Drawing upon multi-sited ethnography, which encompasses qualitative observation in immigrant settlements, neighbourhood mapping, household interviews, archival analysis of planning documents and policy frameworks, and mapping of spatial transformations, I trace how immigrants strategically contested their socio-political invisibility. The concluding analysis contributes to urban theory by demonstrating how liminal urbanisation reveals pathways for decolonising Mediterranean cities through participatory planning, cultural integration initiatives, and structural reforms that recognise immigrants as legitimate city-makers rather than temporary labourers.